THE SAFE SCHOOL POLICIES THAT AFFECT THE DEVEIOPMENT OF A WHITE SCHOOL UNDER THE OFFICE OF SA KAEO PRIMARY EDUCATIONAL SERVECE AREA DISTRICT 1 - Ritcham, Marut; Warabamrungkul, Theerangkoon; Nilkote , Reongwit (Journal of MCU Nakhondhat, 2023)
The objectives of this research were 1) to study the safe school policies that affect the development under the office of sa kaeo primary education service area district 1, 2) to study white school under the office of sa kaeo primary education service area district 1, and 3) To study the relationship between the safe school policies that. with the development under the office towards the office of sa kaeo primary education service area district 1, and 4) To create the safe school policies that affect affects the development under the office of sa kaeo primary education service area district 1. This research is quantitative. Tools and collect data from samples using questionnaires. The sample group consisted of 310 teacher civil servants. The data were analyzed by mean, standard deviation, Pearson correlation and multiple regression analysis. The results showed that 1) The overall skills of the safe school policies that affect the development under the office was at a high level with an average of 4.51. 2) The overall academic administration towards white school under the office was at a high level with an average of 4.52. 3) The safe school policies that affect the development and white school under the office towards school excellence had a high positive relationship with statistical significance at the .05 level, with a multiple correlation coefficient of .853 and a predictive power of .728 .There is 72.80 percent of academic administration towards excellence, can be written as a forecasting equation The forecasting equation in raw score format = -.010 + .851 (X2) + .811 (X3) and the forecasting equation in standard score format y = .880 (X2) + .893 (X3)